Functional modelling of symmetrical multi-pulse auto- transformer rectifier units for aerospace applications - Yang, Tao; Bozhko, Serhiy; Asher, Greg (IEEE, 2015)
This paper aims to develop a functional model of symmetrical multi-pulse Auto-Transformer Rectifier Units (ATRUs) for More-Electric Aircraft (MEA) applications. The ATRU is seen as the most reliable way readily to be applied in the MEA. Interestingly, there is no model of ATRUs suitable for unbalanced or faulty conditions at the moment. This paper is aimed to fill this gap and develop functional models suitable for both balanced and unbalanced conditions. Using the fact that the DC voltage and current are strongly related to the voltage and current vectors at the AC terminals of ATRUs, a functional model has been developed for the asymmetric ATRUs. The developed functional models are validated through simulation and experiment. The efficiency of the developed model is also demonstrated by comparing with corresponding detailed switching models. The developed functional model shows significant improvement of simulation efficiency, especially under balanced conditions.